2005
DOI: 10.1177/0193841x05275389
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Educational Deficiencies of Delinquent and Nondelinquent Students

Abstract: This article assesses the differences in educational deficiencies between a statewide sample of delinquent students and a matched sample of nondelinquent students. Employing a research design that controls for a series of relevant individual and school variables, the study's findings document that delinquent students are characterized by a series of disproportionate educational deficiencies as compared to their nondelinquent student counterparts. Delinquent students were found to attain lower grade point avera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
8

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 39 publications
3
53
0
8
Order By: Relevance
“…For example, poor academic achievement is associated with numerous delinquent activities, including cigarette use (Bryant et al 2004) and alcohol use (Crosnoe 2006). Other research also supports the link between school problems and delinquency (Wang et al 2005). An association has also been found between school performance and multiple victimizations (Holt et al 2007).…”
Section: Schoolmentioning
confidence: 97%
“…For example, poor academic achievement is associated with numerous delinquent activities, including cigarette use (Bryant et al 2004) and alcohol use (Crosnoe 2006). Other research also supports the link between school problems and delinquency (Wang et al 2005). An association has also been found between school performance and multiple victimizations (Holt et al 2007).…”
Section: Schoolmentioning
confidence: 97%
“…55 Moreover, nearly all detained youth eventually return to their communities. 56 Traditional services may then be inaccessible: delinquent youth may not have access to health care 57,58 ; may not attend school regularly 59 and therefore not receive school-based interventions; and may not have a stable caretaker, 60 a requirement for many interventions. 54 Comprehensive evidence-based treatments, such as multisystemic therapy 61 and functional family therapy, 62 address some of these barriers.…”
Section: Figurementioning
confidence: 99%
“…Reviews have found that adolescents with learning disabilities compared to those adolescents without such learning disabilities have two to three times greater risk of being involved in offending activities, as well as higher offending recidivism rates (Matta-Oshima, Huang, Jonson-Reid, & Drake, 2010;Wang, Blomberg, & Li, 2005). This link from the schools to the juvenile courts, and in particular detention and incarceration facilities, has gained the attention and concern of many policy makers and stakeholders.…”
Section: Learning Disabilitiesmentioning
confidence: 99%